Controversies in Cardiology. Part 2. Should I treat a high risk chronic coronary syndrome invasively from the beginning? No, in most cases - Carrasco Rueda, José María (2020)
The definition of high-risk chronic coronary syndrome varies depending on the noninvasive test used to trigger ischemia. The triggering occurs through increased myocardial work and oxygen demand, either through exercise or drugs. The initial approach to the chronic coronary syndrome leads us to discuss in which cases to prioritize an optimal initial medical therapy or to perform an initial invasive procedure of myocardial revascularization. In this article we analyze both approaches based on previous studies carried out to date, where the initial invasive management has not been shown to be superior to initial optimal medical therapy in outcomes such as death or major adverse cardiovascular events.